Association of epicardial and visceral adipose tissue in relation to subclinical cardiac dysfunction in Chinese: Danyang study - Chao Chen; Ming Liu; Fang Yao; Siqi Zhang; Lingkai Zeng; Mulian Hua; Junya Liang; Yun Gao; Xixuan Zhao; Anxia He (BMJ Open)
Objective Our study aims to examine the associations of visceral adipose tissue (VAT) and epicardial adipose tissue (EAT) with subclinical cardiac dysfunction in a Chinese population.Design Cross-sectional.Background EAT and VAT are the most important ectopic fat pools which were previously shown to be associated with subclinical cardiac dysfunction. However, few studies simultaneously measured both EAT thickness and VAT area, and explored their associations with cardiac dysfunction. Our study aims to examine the associations of VAT and EAT with subclinical cardiac dysfunction in a Chinese population.Methods The study subjects were recruited from Danyang County from 2018 to 2019. Using Philips CX50, we recorded EAT thickness at the end-systole in a long-axis view. The subclinical systolic and diastolic function were assessed by two-dimensional speckle tracking, and transmitral and tissue Doppler imaging, respectively. Using Omron HDS-2000, we measured VAT area by dual bioelectrical impedance analysis.Results The 1558 participants (age, 52.3±12.8 years) included 930 (59.7%) women. Compared with women, men had higher VAT area (99.4 vs 70.1 cm2; p<0.0001) but lower EAT thickness (4.02 vs 4.46 mm; p<0.0001). In simple correlation analyses, EAT thickness and VAT area were positively associated with E/e’ ratio (r=0.16 to 0.20; all p<0.0001) and negatively with global longitudinal strain (GLS) and e’ (r=−0.12 to −0.37; all p<0.0001). Furthermore, VAT area was associated with left ventricular ejection fraction (LVEF) (r=−0.14; p<0.0001). After adjustment for confounding factors, the association of EAT with GLS and that of VAT with e’ and E/e’ ratio remained significant (all p≤0.001), whereas the associations of EAT with subclinical diastolic dysfunction and that of VAT with systolic function became non-significant (all p≥0.11). Analyses on further adjustment for LVEF showed similar results.Conclusions Increased EAT thickness was associated with worse subclinical systolic dysfunction, while greater VAT area was associated with early diastolic dysfunction.